Masterpieces of History : The Peaceful End of the Cold War in Europe, 1989 - Thomas Blanton (Central European University Press, 2010)
Twenty years in the making, this collection presents 122 top-level Soviet, European and American records on the superpowers' role in the annus mirabilis of 1989. Consisting of Politburo minutes; diary entries from Gorbachev's senior aide, Anatoly Chernyaev; meeting notes and private communications of Gorbachev with George H.W. Bush, Margaret Thatcher, Helmut Kohl and Francois Mitterrand; and high-level CIA analyses. Complementing the documents is the inclusion for the first time of the proceedings of an extraordinary face-to-face mutual interrogation (with scholars and documents ) in 1998 of Russian and American senior former officials-Gorbachev advisers Anatoly Chernyaev and Georgy Shakhnazarov, Shevardnadze aide Sergei Tarasenko, U.S. Ambassador Jack Matlock and CIA chief Soviet analyst Douglas MacEachin-aimed at assessing and explaining Moscow and Washington's policies during the miraculous year of 1989.